The project COMPASS protocol: Optimizing mindfulness and acceptance‐based behavioral treatment for binge‐eating spectrum disorders. Issue 3 (7th December 2020) - Juarascio, Adrienne S.; Felonis, Christina R.; Manasse, Stephanie M.; Srivastava, Paakhi; Boyajian, Laura; Forman, Evan M.; Zhang, Fengqing
Abstract: Outcomes from cognitive behavioral therapy for binge‐eating spectrum disorders are suboptimal, possibly due in part to deficits in self‐regulation (i.e., the ability to control behavior in pursuit of long‐term goals despite internal challenges). Mindfulness and acceptance‐based treatments (MABTs) integrate behavioral treatment with psychological strategies designed to enhance self‐regulation, yet little is known about how and for whom they are effective. The present study will utilize the multiphase optimization strategy to identify which of four MABT components (mindful awareness, distress tolerance, emotion modulation, values‐based decision making) to include in a fully powered clinical trial. Participants ( n = 256) will be randomized to 16 sessions in one of 16 conditions, each a different combination of MABT components being included or excluded from a base behavioral treatment. Our primary aim is to evaluate each component's independent efficacy on disordered eating symptoms. Our secondary aims are to confirm each component's target engagement (i.e., whether each component improves the targeted variable and outcomes), and test that each component's efficacy is moderated by baseline weaknesses in the same component (e.g., that participants with poor distress tolerance at baseline benefit most from the distress tolerance component). Our exploratory aim is to quantify the component interaction effects.